Nitrogen fertilizer fate after introducing maize and upland-rice into continuous paddy rice cropping systems - Fuhrmann, Irabella; He, Yao; Lehndorff, Eva; Brüggemann, Nicolas; Amelung, Wulf; Wassmann, Reiner; Siemens, Jan (Elsevier, 2018)
Water scarcity and economic incentives favor the introduction of upland crops into permanent paddy rice systems during dry seasons. However, introducing upland crops into permanently flooded cropping systems temporarily changes soil conditions from anaerobic to aerobic, affecting nitrogen (N) dynamics profoundly. We hypothesized that under maize and dry rice, total fertilizer 15N recovery in soil as well as the immobilization of fertilizer 15N in microbial residues is reduced compared with continuous paddy rice cropping. Furthermore, we expected enhanced emissions of fertilizer 15N in form of nitrous oxide (N2O) under maize and dry rice. To test these hypotheses, we traced the fate of a 15N-urea pulse in a field experiment in the Philippines with three different crop rotations: continuous paddy rice, paddy rice – dry rice, and paddy rice – maize for two years. Indeed, the 15N recovery in the first 5 cm of bulk soil was lowest in the paddy rice – maize rotation (arithmetic mean with standard error: 19.2 ± 1.8% of applied 15N), while twice as much was recovered in the first 5 cm of bulk soil of the continuous paddy rice cropping systems (37.8 ± 2.2% of applied 15N) during the first dry season. The 15N recovery in the plant biomass (shoots and roots) in the continuous paddy rice cropping was 13% larger than in the dry rice plant biomass and 5% larger than in the maize plant biomass during the first dry season. Fertilizer 15N remained longest in paddy rice – maize (mean residence time = 90 ± 25 days) and in continuous paddy rice (mean residence time = 77 ± 30 days), compared with dry rice – paddy rice rotation (mean residence time = 16 ± 5 days). After 2 years, 10% (paddy rice – dry rice, paddy rice – maize) to 23% (continuous paddy rice) of the applied fertilizer 15N were still stored in soil. The largest fraction of this 15N was immobilized by soil microbes, which stored 3–4% of applied 15N in the form of amino sugars as specific cell wall constituents, in all cropping systems. Nevertheless, introducing upland crops into continuous paddy rice systems likely increased N leaching losses and resulted in initial losses of urea- 15N to N2O, which thus has to be considered in climate smart mitigation strategies